2011
DOI: 10.1016/j.ejogrb.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depression, anxiety, self-esteem, and health behaviour on neonatal outcomes in a population-based Hungarian sample

Abstract: Lower level of maternal self-esteem possibly leads to a higher level of maternal stress which may reduce fetal growth via physiologic changes. Gender differences in associations between demographic factors and neonatal outcome measures indicate differences in fetal development between boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 38 publications
1
38
1
2
Order By: Relevance
“…Of the 27 English language studies that examined the relationship between depression during pregnancy and PTB [935], 12 found that depression increased risk of PTB (odds ratios range 1.3–4.9) [24,2634] or decreased GA at birth [25,35] while the remainder found no effect [9,1123]. All but one [30] were prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 English language studies that examined the relationship between depression during pregnancy and PTB [935], 12 found that depression increased risk of PTB (odds ratios range 1.3–4.9) [24,2634] or decreased GA at birth [25,35] while the remainder found no effect [9,1123]. All but one [30] were prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that antenatal period is a time of increased liability to mental disorders. The most common psychiatric illnesses during pregnancy and the postpartum period are stress and anxiety disorders (Bödecs et al, 2011). According to Andersson et al, (2004) and Berle et al, (2005), about 10% of pregnant women meet the criteria for anxiety disorders in Sweden and Norway respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies which have examined the reverse causal effect by looking at antenatal depression as a risk factor for neonatal complications have found antenatal depression was associated with neonatal smallfor-gestational age (AOR=1.19 p=0.02) and low Apgar scores (AOR=1.74 p=0.01) (Goedhart et al, 2010). By contrast another study found that no association existed between maternal antenatal depression, and anxiety and health behaviours and neonatal outcomes (Bodecs et al, 2011). Overall, there was limited, available evidence relating to pregnancy/birth complications and/or neonatal outcomes being risk factors for women's poor mental health in the postnatal period.…”
Section: Birth Outcomesmentioning
confidence: 96%